Chinese Medicines as an Adjuvant Therapy for Unresectable Hepatocellular Carcinoma during Transarterial Chemoembolization: A Meta-Analysis of Randomized Controlled Trials. (17th July 2013) - Cheung, Fan; Wang, Xuanbin; Wang, Ning; Yuen, Man-Fung; Ziea, Tat-chi; Tong, Yao; Wong, Vivian Taam; Feng, Yibin
Abstract : Objective . To conduct a comprehensive PRISMA-compliant systematic review and meta-analysis to evaluate the efficacy and safety of Chinese medicines (CMs) as an adjuvant therapy for unresectable HCC during transarterial chemoembolization (TACE). Methods . Main databases were searched up to October 2012 for randomized controlled trials (RCTs) evaluating the effects of CMs plus TACE on unresectable HCC compared with TACE alone. References of relevant reviews and eligible studies were also assessed. Risk ratios with 95% confidence intervals and mean difference were calculated. Heterogeneity and publication bias were examined. Results . Sixty-seven trials ( N = 5, 211) were included in the meta-analysis. Sensitivity analysis and random-effects model were performed for assessing significant heterogeneity. CMs plus TACE showed beneficial effects on tumor response, survival at 6, 12, 18, 24, and 36 months, quality of life, and TACE toxicity reduction compared with TACE alone. Conclusion . The results show that the use of CMs may increase the efficacy and reduce the toxicity of TACE in treating patients with unresectable HCC. These findings suggest that CMs could be considered as an adjuvant therapy for unresectable HCC patients during TACE. Larger-scale RCTs using standard methods and long-term follow-up are warranted to confirm these findings.